Readiness of ICE Institute Courses Based on ICE-I QAT with Quality Assurance Criteria - Afriani, Afriani; Dewi, Laksmi; Hariwibawanto, Hariwibawanto; Purbojo, Rijanto; Emilzoli, Mario; Asih, Irsanti Widuri; Arwan, Juwintar Febriani (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to evaluate the readiness of online courses offered by the ICE Institute based on seven quality assurance dimensions developed through ICE-I QAT. These seven dimensions include course information, instructor information, technology and learning tools, learning materials, interaction, assessment, and evaluation. The method used was descriptive quantitative by using instrument quality assurance criteria was developed by ICE-I. Sample of this research were 77 courses and were curated by the partner universities collaborating with the ICE Institute in 2024. The results show variability in the readiness levels of the courses across each dimension. For example, in the course information dimension, only 45 out of 77 courses met the minimum standards, while in the assessment dimension, only 23 courses met the standards. These findings indicate that many courses still need quality improvement, particularly in learning materials, interaction, and assessment. The discussion highlights the importance of providing clear information, effective use of learning technology, and comprehensive instructional materials to enhance student engagement and course completion. The study concludes that improving the quality of online courses is essential to support effective and meaningful distance learning at the ICE Institute.